Cold start performance analysis of PEMFC with different assisted heating strategies - Wenhao Li; Jianjun Yang; Changqing Du; Jie Zhao; Qianqian Xin; Fuwu Yan (Case Studies in Thermal Engineering)
Large-scale use of proton exchange membrane fuel cell (PEMFC) is restricted by the challenge of cold start. A three-dimensional, transient, multiphase flow cold-start model is established to investigate the effects of different assisted heating strategies. The variations of ice volume fraction and temperature distribution of catalyst layer and their influences on cold start performance of PEMFC are discussed in detail, under coolant-assisted heating strategy, air-assisted heating strategy and the combination of two strategies at −20 °C. The results show that coolant-assisted heating strategy has significant effect on the cold start performance. There is an appropriate coolant flow velocity and heating power to balance cold start performance and energy consumption. Air-assisted heating strategy has minimal improvement on the cold start performance. Moreover, an interesting point is that on the basis of coolant-assisted heating adoption, the heat brought by the air-assisted heating although not much but can effectively improve water storage capacity of the ionomer. This makes the combination of two strategies has more excellent cold start performance, namely, catalyst layer's ice volume fraction decreases by 7.7 % and cold start time shortens by 2 s, compared to coolant-assisted heating, which provides valuable information for practical cold start strategy design of PEMFC.